2014
DOI: 10.1155/2014/210327
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Investigation of Pyrano[2,3-d]pyrimidine Formation in the Presence of Catalyst under Novel One-Pot Three-Component Reaction

Abstract: Sodium acetate was applied as an efficient catalyst for the one-pot, three-component condensation reactions consisting of 4-nitrobenzaldehyde 2, malononitrile 3, and thiobarbituric acid 1. Use of nontoxic reaction components, short reaction times, environmental, easy work-up, and high yields are some remarkable advantages of this method. Kinetics and mechanism of the reaction were spectrally studied and the second order rate constant (k ovr = k 1 ) was automatically calculated by the standard equations contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The same reaction conditions was utilized by Habibi-Khorassani et al 132 This group of co-workers reported kinetic and mechanistic studies on the one-pot synthesis of 7-amino-5-(4-nitrophenyl)-4-oxo-2-thioxo-1,3,4,5-tetrahydro-2 H -pyrano[2,3- d ]-pyrimidine-6-carbonitrile 91 ( Scheme 66 ). They used equimolar (1 mmol) reaction of 1 with 12 and 11 in sodium acetate with aqueous ethanol at 50 °C.…”
Section: Synthesis Of 5-aryl-substituted Pyrano[23- D ...mentioning
confidence: 99%
“…The same reaction conditions was utilized by Habibi-Khorassani et al 132 This group of co-workers reported kinetic and mechanistic studies on the one-pot synthesis of 7-amino-5-(4-nitrophenyl)-4-oxo-2-thioxo-1,3,4,5-tetrahydro-2 H -pyrano[2,3- d ]-pyrimidine-6-carbonitrile 91 ( Scheme 66 ). They used equimolar (1 mmol) reaction of 1 with 12 and 11 in sodium acetate with aqueous ethanol at 50 °C.…”
Section: Synthesis Of 5-aryl-substituted Pyrano[23- D ...mentioning
confidence: 99%
“…Thus, arsonium ylides react frequently in the form of ylide B ( Figure 2) faster than phosphonium ylides. Although the kinetics and mechanistic investigations of some reactions with TPP have been reported previously [6][7][8][29][30][31][32][33], no attempts for similar reactions with TPA have been reported. www.prkm.co.uk…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid (HL) is considered as a top 12 biobased platform molecule and may serve as a useful precursor chemical for producing green solvents and polymers [36,37] with wide usage in pharmaceuticals, cosmetics and food packaging [38,39]. In continuation of our ongoing programme in the kinetics of multi-component reactions [40][41][42][43][44][45][46][47][48][49][50], here we investigated the kinetics and mechanism of the reactions between para-substituted anilines 1 and dimethyl acetylenedicarboxylate (DMAD) (2) with benzaldehyde derivatives 3 for the formation of 3,4,5-substituted furan-2(5H)-ones using HL as an efficient catalyst in ethanol at ambient temperature, with good yields. Synthetic details of this reaction have been published earlier by Maghsoodlou and co-workers [51] (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%